MIKE MEYERS' COMPTIA A+ CORE 2 CERTIFICATION PASSPORT EXAM 220-1102 - Gilster, Ron (MCGRAW-HILL EDUCATION, 2023)
Accelerated coverage of every topic on the 2022 version of the A+ Core 2 exam from CompTIA Get on the fast track to becoming CompTIA A+ certified with this affordable, portable study tool. Inside, certification training gurus Mike Meyers and Ron Gilster guide you on your exam preparation path, providing expert tips and sound advice along the way. With an intensive focus on only what you need to know to pass the CompTIA A+ 220-1102 exam, this certification passport is your ticket to success on exam day. TECHNICAL BULLETS: Inside:Reviews and descriptions of the major features of Windows 10/11, macOS, and Linux operating systems Information and tips on operating systems, networking, and feature configurations Enhanced coverage of mobile device setup and troubleshooting Enhanced coverage of computer security Practice questions and content review after each objective prepare you for exam mastery Covers all exam topics, including how to: Configure system and application software to work with CPUs, RAM, BIOS, and other personal computer components Install, configure, and maintain operating systems and apps Set up, upgrade, and maintain Windows 10/11 Troubleshoot and fix software problems Configure and secure mobile device software Protect your personal computer and your network Properly and safely diagnose, resolve, and document common software issues Understand the basics of scripting, cloud technologies, virtualization, and multi-OS deployments in working in home, SOHO, and corporate environments Online content includes: Practice exam for 220-1102 Free sample of video training from Mike Meyers Free sample of interactive labs from Mike Meyers Mike Meyers' favorite PC tools and utilities.